Acute Abdominal Pain: Recognition and Management of Constipation in the Emergency Department. Issue 10 (October 2017) - Norbedo, Stefania; Bassanese, Giulia; Barbieri, Francesca; Barbi, Egidio
Abstract : Objective: The main aim of the study was to investigate the incidence and the clinically relevant features of functional constipation in patients evaluated for acute abdominal pain in a tertiary care pediatric emergency department. Methods: This is a retrospective study. We analyzed 4394 medical records and recorded the information (demographics, triage code, symptoms, medical history, physical evaluation, laboratory tests, radiological studies, procedures, and treatments) of all patients admitted for acute abdominal pain to the emergency department of the IRCCS Burlo Garofolo, Trieste, during 2010 to 2013. Results: In this study, a quarter of patients (1020) presenting in the emergency department with acute abdominal pain were affected by functional constipation. Acute pain associated with functional constipation is generally rated from moderate to severe, and the location of the pain on physical evaluation was not a sufficient criterion to guide diagnosis. Isolated vomiting may be present in a minority of cases. Digital rectal exploration was never performed; the majority of patients were treated by means of an enema with prompt relief. Six percent of patients with constipation underwent radiological studies. Conclusions: This study confirms that the medical history provides a pivotal role in the diagnosis of functional constipation. Digital rectal exploration and x-rays should be avoided in this setting, whereas an enema plays a useful diagnostic and therapeutic role in our study patients.